Functions of interactive multimedia tools in preschool teaching - Matilde Bolaño García (Universidad del Magdalena, 2017)
The development of information systems during the last decade has strenghten the visibility of interactive multimedia tools (IMT) as a didactic support in several areas. In this vein, this article aimed at determining the role of the Interactive Multimedia Tools as used by teachers at preschool education in institutions belonging to the municipality of Santa Marta-Colombia. The study was based on a positivist approach, was designed as a descriptive research with non-experimental field research. As for the target population, it consisted of 38 preschool teachers from the above mentioned institutions. The data collection technique was observation by survey and the instrument was the questionnaire. Data analysis resulted in the conclusion that IMT are used in three different ways by preschool teachers. Firstly, to explore and experiment, secondly to instruct or train (both of them little used) and thirdly, to motivate - more common use among researched teachers.